Effort to Increase Acupressure Massage Skills in Health Cadres and Nurses in the Cimahi City - Galih Jatnika; Achmad Setya Roswendi; Lilis Rohayani; Musri Musri; Argi Virgona Bangun; Nadirawati Nadirawati; Meivi Sesanelvira; Oyoh Oyoh; Setiawati Setiawati; Nunung Nurjanah; Siti Dewi Rahmayanti (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Acupressure is now included as a nursing intervention and is recognized in more than 40 countries. The Nursing science strata S1 Study Program and the Nurse Profession Study Program, Faculty of Technology and Health, Unjani Cimahi have advantages in the field of complementary acupressure therapy. Acupressure therapy has been applied to the learning process, laboratory practice and practice in the community, but for clinical instructors as guides for learning in practice areas and in the community, it is still lacking. There is a need for training efforts given to puskesmas nurses and health cadres in the Cimahi City area to prepare prospective clinical instructors for student mentors in practice areas. Acupressure massage training was given to 14 nurses and health cadres in the Cimahi City area for 3 days through lecture and demonstration methods by resource persons and ended with a practical exam. The results of the training activities obtained that the average skill before being given training was 67.14 and the average skill after being given training was 89.07. There was a significant increase in skills (p value 0.001) in puskesmas nurses and health cadres in the Cimahi City area. It is recommended for cadres and nurses to apply acupressure massage skills in their area as a complementary therapy to overcome various symptoms and disorders caused by diseases experienced by the community.